2005
DOI: 10.1063/1.1923165
|View full text |Cite
|
Sign up to set email alerts
|

Desorption dynamics of oxide nanostructures fabricated by local anodic oxidation nanolithography

Abstract: We studied the properties of GaAs oxides which were grown by local anodic oxidation (LAO) nanolithography using an atomic force microscope. We find that the LAO structures desorb under irradiation with soft x-rays (130eV). We analyzed the desorption process in detail by time-resolved photoelectron spectroscopy. We observe that even in the first stages of light exposure the LAO oxide is mainly composed of Ga2O, with a small fraction of Ga2O3 and As oxides. The As oxides are located only in the surface layers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…21 Usually heights are measured with respect to the substrate baseline, consequently reported oxide heights differs from the true oxide thickness. In Si approximately 60% of the oxide is above the substrate baseline.…”
Section: Local Oxidation Nanolithographymentioning
confidence: 99%
“…21 Usually heights are measured with respect to the substrate baseline, consequently reported oxide heights differs from the true oxide thickness. In Si approximately 60% of the oxide is above the substrate baseline.…”
Section: Local Oxidation Nanolithographymentioning
confidence: 99%
“…Formation of Ga oxides results in two components on the low kinetic energy side of the GaAsrelated Ga 3d peak, shifted by -0.7 and -1.4 eV, whereas the multiple oxidation states of As result in up to five new components with shifts ranging between -0.7 and -4.5 eV [31,32]. The As oxides may also undergo partial photon-induced reduction, which complicates the interpretation of the As 3d spectra [29,33]. The smaller chemical shifts, fewer oxide components and higher stability of Ga oxides makes the Ga 3d spectra more suitable for exploring charging effects in the oxidized NWs.…”
Section: Oxidation Effects On the Conductivity Of Gaas Nwsmentioning
confidence: 99%
“…14͒ and GaAs. [15][16][17] In the case of LAO on Si, we found that the LAO oxide consists of SiO 2 whose properties are similar to those of thermally grown SiO 2 . The study of the chemical composition of LAO oxides grown on GaAs revealed that it is mainly composed of Ga oxides with a small amount ͑10%͒ of As oxides located in the topmost layers of the LAO structures.…”
Section: Introductionmentioning
confidence: 69%